Lepidochitona turtoni - Sirenko, Boris (Zenodo, 2023)
Lepidochitona turtoni (Ashby, 1928) (Figs 1–8) Trachydermon ( Craspedochilus ) turtoni Ashby 1928: 80, pl. 6, figs 5–8; Ashby 1931: 16, pl. 2, figs 20–23. Trachydermon turtoni Turton 1932: 209; Ashby & Cotton, 1933: 320. Lepidochitona ( L .) turtoni Kaas & Van Belle 1985: 108, fig. 50, map 5. Lepidochitona turtoni Sirenko & Hayes 1999: fig. 1I–M, 3B, 4A–D. Type material : Turton Collection 1453 (fide Ashby & Cotton 1933). Type locality : South Africa, Port Alfred. Material examined. 96 spms. Indian Ocean , South Africa, Chelsea Point, 34˚2’46.1’’S, 25˚38’4.6”E, 2 m, on abalone shell, 1 spm, BL 5.0 mm, 19.01.1996, leg. B. Sirenko; Atlantic Ocean , False Bay, Oatlands, 34˚12’29.42’’S, 18˚27’46.48”E, intertidal, stones on sand, 1 spm, BL 9.2 mm, 16.03.1996, leg. B. Sirenko & I. Smirnov; Rocklands Point, 34˚12’59.04’’S, 18˚27’57.31”E, intertidal–0 m, stones on sand, 5 spms, BL 7.0–8.0 mm, 16.03.1996, leg. B. Sirenko & I. Smirnov; Boulders, 34˚11’49.20’’S, 18˚27’3.60”E, intertidal–0 m, stones on sand, 2 spms, BL 5.5–6.0 mm, 17.03.1996, leg. B. Sirenko & I. Smirnov; Glencairns, 34˚9’48’’S, 18˚25’47”E, intertidal–0 m, stones in tide pool, 9 spms, BL 4.0–8.0 mm, 23– 24.03.1996, leg. B. Sirenko & I. Smirnov; Glencairns, 34˚9’48’’S, 18˚25’47”E, intertidal–0 m, stones in tide pool, 2 spms, BL 7.0 mm, 11.03.2000, leg. B. Sirenko & I. Smirnov; Oatlands, 34˚12’29.42’’S, 18˚27’46.48”E, 2.0 m, stones on rocks, 1 spm, BL 7.0 mm, 03.02.2007, leg. B. Sirenko;, Kommetjie, 34˚8’25’’S, 18˚19’45.1”E, intertidal–0 m, stones in tide pool, 5 spms, BL 7.0–9.0 mm, 20.03.1996, leg. B. Sirenko & I. Smirnov; Klein-Stagkop Point, 34˚9’48’’S, 18˚25’47”E, intertidal, stones on rocks, 50 spms, BL 3.0–9.0 mm, 19– 22.03.1996, leg. B. Sirenko & I. Smirnov; Hout Bay, 34°2′S 18°21′E, intertidal, stones on rocks in tide pools, 20 spms, BL 4.0–9.0 mm, 12.03.2000, leg. B. Sirenko & I. Smirnov. Distribution. From Port Alfred (south Indian Ocean) to Hout Bay (south Atlantic Ocean), intertidal to 2 m. ...